Pathophysiological roles of FGF signaling in the heart - Itoh, Nobuyuki; Ohta, Hiroya (Frontiers in Physiology, 2013)
Cardiac remodeling progresses to heart failure, which represents a major cause of morbidity and mortality. Cardiomyokines, cardiac secreted proteins, may play roles in cardiac remodeling. Fibroblast growth factors (FGFs) are secreted proteins with diverse functions, mainly in development and metabolism. However, some FGFs play pathophysiological roles in cardiac remodelling as cardiomyokines. FGF2 promotes cardiac hypertrophy and fibrosis by activating MAPK signaling through the activation of FGF receptor (FGFR) 1c. In contrast, FGF16 may prevent these by competing with FGF2 for the binding site of FGFR1c. FGF21 prevents cardiac hypertrophy by activating MAPK signaling through the activation of FGFR1c with β-Klotho as a co-receptor. In contrast, FGF23 induces cardiac hypertrophy by activating calcineurin/NFAT signaling without αKlotho. These FGFs play crucial roles in cardiac remodeling via distinct action mechanisms. These findings provide new insights into the pathophysiological roles of FGFs in the heart and may provide potential therapeutic strategies for heart failure.